Criatividade e abertura de espaço: um estudo junguiano - Carvalho, Olavo Virgílio de (2012)
The present study aimed to investigate the concept of creativity in analytical psychology. We investigated the Collected Works and letters of Carl Gustav Jung and also books and articles of post-Jungian authors who contributed to the development of the theme. It was highlighted that images have a legitimate existence and are a spontaneous phenomenon of the psyche. Thereby it was emphasized that the contents of the psyche have the same value of reality that the material world. The analytical psychology defines creativity as something natural, a autonomous complex and fundamental quality of the psyche. The work increased the understanding of creativity as open space for the images of the unconscious to present themselves